Malawi Poverty and Vulnerability Assessment : Investing in Our Future, Synthesis Report - World Bank (Washington, DC, 2012)
This study builds a profile of the status of poverty and vulnerability in Malawi. Malawi is a small land-locked country, with one of the highest population densities in Sub-Saharan Africa, and one of the lowest per capita income levels in the world. Almost 90 percent of the population lives in rural areas, and is mostly engaged in smallholder, rain-fed agriculture. Most people are therefore highly vulnerable to annual rainfall volatility. The majority of households cultivate very small landholdings, largely for subsistence. As a result, poverty is pervasive and not merely the situation of the lowest economic groups. Therefore, while this report focuses on the least-well-off sections of the population, the analysis provides valuable information to accelerate wealth creation and economic growth for the whole of Malawi. This synthesis report presents the main findings and policy recommendations stemming from the analysis. Due to the length and detail of this study, the 'full report' presenting the detailed analysis and results underpinning these policy recommendations is available as a separate publication. This report highlights some of the key characteristics and causes of poverty in Malawi, and focuses on the main sources of risk affecting households, namely food insecurity and health shocks. Based on these findings, the report goes on to develop a set of policy recommendations for widely shared growth and poverty reduction, and for enabling the most vulnerable to make a living. Finally, the report also provides recommendations for strengthening the monitoring and evaluation systems of poverty reduction strategies, so that policy makers and Malawian society can better track the effectiveness of the policies pursued, and inform future policy choices.